Secondary Involvement of the Uterine Cervix by Nongynecologic Neoplasms: A Detailed Clinicopathologic Analysis. (December 2020) - Turashvili, Gulisa; Samore, Wesley R.; Oliva, Esther; Ioffe, Olga; Riddell, Robert; Park, Kay J.; Horn, Lars-Christian
Abstract : Secondary involvement of the uterine cervix by nongynecologic neoplasms is rare accounting for <2% of metastases to the gynecologic tract. This study aimed to analyze the clinicopathologic features of cervical involvement by nongynecologic malignancies. A total of 47 cases were identified including 39 (83%) carcinomas, 6 lymphomas (12.8%), and 2 (4.2%) cutaneous malignant melanomas. The most common primary site of origin among carcinomas was the gastrointestinal tract (27, 69.2%), followed by breast and urothelium (5 each, 12.8%), gallbladder, and lung (1 each, 2.6%). The gynecologic tract was involved at the presentation in 16 patients (34%), including 5 (10.6%) with the cervix being the first site, 7 (14.9%) with synchronous involvement of the cervix and other gynecologic sites, and 4 (8.5%) with the involvement of other gynecologic sites before the cervical presentation. Patients with lymphoma were younger compared with those with carcinoma (43.7 vs. >50.5) ( P =0.01). Mean time to identification of cervical metastases was <1 year for gallbladder carcinoma, melanomas, and gastrointestinal signet ring cell carcinomas ( P =0.03). Features that varied with different types of metastatic tumor included lymphovascular space invasion, depth of stromal invasion, growth pattern (glands lacking architectural complexity, cribriforming, solid), presence of goblet cells, and signet ring cells, degree of cytologic atypia, and overall findings mimicking a benign/noninvasive process ( P ⩽0.027). Six tumors (12.8%) were initially misdiagnosed as cervical primary. Metastatic nongynecologic tumors can mimic primary in situ or invasive neoplasms in both ectocervix and endocervix. In patients with a known prior malignancy, the clinical history with ancillary studies and a high level of suspicion are crucial to ensure accurate diagnosis.